Implementation of wound care for mellitus diabetes feet in Medan Johor - Rusdiana; Savira, Maya (Talenta Publisher, 2019)
In this community service education has been carried out to some cadres in the work area of Medan Johor health center, where the education we provide in the form of prevention of injuries to the feet of diabetes mellitus. The educational facilities we use in the form of lectures using LCD projectors and also giving leaflets to cadres. In our service, we also conduct a free examination in the form of a physical examination, which is blood pressure, height and weight for cadres and a laboratory examination, which is checking blood sugar, uric acid and cholesterol. Educate how to take care of your feet and diabetes exercises. The targets of this program are cadres and people with diabetes who are in the family and community. Through this education it is expected to avoid complications of diabetic foot injuries so that the quality of life becomes better. At the end of the implementation of this community service we provide leaflets to cadres or sufferers of type 2 DM that we educate and also give them to the Puskesmas also we provide posters and also measuring devices KGD, and glycemic control testing tools to be used by cadres or people with type 2 diabetes.